Atomic structure of hot compressed borosilicate glasses. Issue 11 (9th August 2020) - Ding, Linfeng; Lee, Kuo‐Hao; Zhao, Tongyao; Yang, Yongjian; Bockowski, Michal; Ziebarth, Benedikt; Wang, Qingwei; Ren, Jinjun; Smedskjaer, Morten M.; Mauro, John C.
Abstract: Borosilicate glasses have been in widespread use for over a century; however, a detailed understanding of the structural response to densification is still lacking. In this work, two commercial borosilicate glasses, viz., SCHOTT N‐BK7 ® (N‐BK7) and Borofloat33 ® (Boro33), are hot compressed up to 2 GPa with nitrogen gas, and the structural response to this densification is explored via 11 B solid‐state nuclear magnetic resonance (NMR) spectroscopy and classical molecular dynamics (MD) simulations. The molar volume ( V m ) of N‐BK7 and Boro33 decreases ~5% and ~10%, respectively, as a result of hot compression at 2 GPa. The NMR results demonstrate the presence of three different types of fourfold coordinated boron species (B [4] ), which are confirmed in MD simulations to be B 1 4 (0B, 4Si [4] ), B 2 4 (1B [3], 3Si [4] ), and B 3 4 (1B [4], 3Si [4] ) (where subscripts represent different B [4] types and brackets indicate the next nearest neighbors (NNN)). The NMR results also show that the fraction of B [4] increases by ~13% in N‐BK7 glass upon hot compression at 2 GPa via the trigonal boron to tetrahedral boron (B [3] to B [4] ) conversion, while the fraction of B [4] in Boro33 glass only increases by ~2% at the same pressure, despite the fact that the V m decrease in N‐BK7 is double that of Boro33. The MD simulations capture the experimental trends in B [4] populations, despite an underestimation of the B [4] increase of N‐BK7 (only ~6%) at 2 GPa. Moreover, the MD simulations suggest that the V m reduction is a linear function of bond angle change and the fraction of Si‐O‐Si and B [4] ‐O‐Si. The modifiers and boron coordination conversion also influence the volume densification of borosilicate glasses by increasing the difficulty of bond bending, decreasing the bond lengths, and increasing the population of B [4] ‐O‐Si linkages. Finally, the B [4] to B [4] conversion, that is, B 2 4 (1B [3], 3Si [4] ) and B 3 4 (1B [4], 3Si [4] ) to B 1 4 (0B, 4Si [4] ), is observed in hot compressed N‐BK7 and Boro33 from NMR and qualitatively confirmed in MD.